Performance Evaluations in Audit Firms: Evaluation Foci and Dysfunctional Behaviour. Issue 1 (4th November 2016) - Johansen, Thomas Riise; Christoffersen, Jeppe
Abstract : Previous research has only minimally examined the association between the behaviour and performance evaluations of individual auditors beyond the use of efficiency‐focused evaluations. We examine the association between dysfunctional auditor behaviour and three evaluation foci: an efficiency focus, a client focus and a quality focus. Our results, which are based on questionnaire responses from 196 auditors, demonstrate that an efficiency focus is not associated with dysfunctional behaviour. A client focus is found to be associated with dysfunctional behaviour. Finally, and perhaps most importantly, our results show that it seems possible to limit dysfunctional behaviours through a quality focus in performance evaluations. Our results provide insights of use to practitioners and regulators on how performance evaluations may not only induce but also reduce dysfunctional auditor behaviours.